Digital health implementation in Australia: A scientometric review of the research - Michelle A. Krahe; Sarah L. Larkins; Nico Adams (Digital Health)
Objective Australia is committed to establishing a digitally enabled healthcare system that fosters innovation, strengthens data capabilities, and establishes a foundation for future digital health reform. This study provides a comprehensive overview of digital health implementation research in Australia, employing scientometric analysis and data visualization. We assess the existing knowledge base, identify key research areas and frontier trends, and explore their implications for healthcare delivery in rural and remote settings. Methods A systematic search of the Web of Science Core Collection database was conducted for relevant documents up to December 31, 2023. Analysis of annual growth patterns, journals, institutional and authorship contributions, reference co-citation patterns, and keyword co-occurrence was conducted using scientometrics to create outputs in the form of graphs and tables. Evolutionary analyses were undertaken to delineate the current knowledge base, predominant research themes, and frontier trends in the field. Results A total of 196 documents related to digital health implementation in Australia were identified, demonstrating sustained growth since 2019. The evolution of the field is characterized by four distinct phases, with a pronounced focus on telehealth, particularly in the context of the COVID-19 pandemic. ‘Remote health’ emerged as a significant area of contemporary interest. Conclusions This scientometric study contributes to our understanding of digital health implementation research in Australia. Despite a considerable body of research, there remains a relative paucity of studies focused on implementation in underserved rural and remote areas which arguably stand to benefit the most from digital health advancements. Continued research in this field is crucial to ensure equitable access to the benefits offered by digital health innovations.